2000
DOI: 10.1038/sj.ejcn.1600939
|View full text |Cite
|
Sign up to set email alerts
|

Designer egg evaluation in a controlled trial

Abstract: Objective: To evaluate the ability of designer eggs enriched in vitamin E, lutein, selenium (Se) and docosahexaenoic acid (DHA) to deliver micronutrients to the human in a palatable and visually acceptable form. Design: Double-blind, placebo-controlled trial, two treatment groups balanced for sex and age. Setting: Department of Biochemistry and Nutrition, SAC, Scotland. Subjects: Forty healthy adult volunteers completed the study. Volunteers were recruited among staff of the Scottish Agricultural College Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 69 publications
5
68
2
3
Order By: Relevance
“…Of the possible reasons for the lower response, fat intake was not mentioned by Surai et al 36 and in an 8-week study, there may have been changes in the intake or type of vegetables consumed during that period. Neither fat intake nor the background dietary intake was controlled.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Of the possible reasons for the lower response, fat intake was not mentioned by Surai et al 36 and in an 8-week study, there may have been changes in the intake or type of vegetables consumed during that period. Neither fat intake nor the background dietary intake was controlled.…”
mentioning
confidence: 97%
“…The second study shown in Table 2 also lacked a pure lutein control group with which to assess relative bioavailability 36 . The authors recruited two groups of subjects to which they fed one control or one lutein-enriched egg per d for 8 weeks.…”
Section: Bioavailability Of Lutein and Zeaxanthin From Eggsmentioning
confidence: 99%
“…In the same perspective, research activities are on record to evaluate the ability of designer eggs enriched with certain nutrients (such as vitamin E, lutein, selenium, docosahexaenoic acid, etc.) to deliver protein, fats, and micronutrients to the human in visually acceptable form (Miranda et al, 2015;Surai, MacPherson, Speake, & Sparks, 2000). As such, designer egg, with altered nutrient composition, is considered as a new type of functional food.…”
Section: Composition Of Egg Carotenoidsmentioning
confidence: 99%
“…In fact, the dietary matrix and the type of lutein are important factors that affect lutein absorption, indicating that the egg yolk is the most effective way to increase lutein bioavailability, although the amounts are relatively lower than other luteinrich vegetables including spinach (Handelman et al, 1999;Surai et al, 2000).…”
Section: Introductionmentioning
confidence: 99%